2013
DOI: 10.3109/1547691x.2013.835891
|View full text |Cite
|
Sign up to set email alerts
|

Expression kinetics of miRNA involved in dermal toluene 2,4-diisocyanate sensitization

Abstract: Allergic disease is an important occupational health concern, with work-related asthma and allergic contact dermatitis being the most frequently diagnosed occupational illnesses. Diisocyanates, particularly toluene 2,4-diisocyanate (TDI), have been the leading cause of occupational asthma for many years. Understanding the mechanisms behind allergic disease is critical for treatment and prevention. Recently, the study of post-transcriptional regulation by microRNAs (miRNA) has shed light on mechanisms of allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Preliminary studies suggest that mouse serum albumin, cytoskeletal, and cuticular keratins are primary targets for haptenation upon dermal exposure. Results from our previous study (Anderson et al, 2013) and from the data presented here suggest that it is likely that the TDI exposure dose may play a critical role on the nature of allergic sensitization. The data from animals exposed to 4% TDI also suggest that general irritation caused by the chemical reactivity with skin may also drive such a response.…”
Section: Figmentioning
confidence: 55%
See 2 more Smart Citations
“…Preliminary studies suggest that mouse serum albumin, cytoskeletal, and cuticular keratins are primary targets for haptenation upon dermal exposure. Results from our previous study (Anderson et al, 2013) and from the data presented here suggest that it is likely that the TDI exposure dose may play a critical role on the nature of allergic sensitization. The data from animals exposed to 4% TDI also suggest that general irritation caused by the chemical reactivity with skin may also drive such a response.…”
Section: Figmentioning
confidence: 55%
“…Previously, studies in our laboratory demonstrated that a single dermal dose of 4% TDI is sufficient to sensitize animals and promote a mixed Th 1 /Th 2 response highlighted by the cytokines IL-4, IL-5, IL-13, and IFN␥ (Anderson et al, 2013). Furthermore this dose was sufficient to promote increased serum IgE levels in these animals.…”
Section: Figmentioning
confidence: 84%
See 1 more Smart Citation
“…Animals (n = 4–5) were exposed to a single dose of 0.5–4% TDI (v/v) on the dorsal surface of each ear (25 μl per ear). The highest concentration (4% v/v; the maximum sensitizing concentration with minimal toxicity) and dosing regimen was previously shown to induce sensitization (Anderson et al ., 2013) and sensitization was confirmed in the lower dose based on total serum IgE levels and dLN allergic cytokine mRNA expression (0.5% v/v; data not shown). Acetone was selected as the vehicle control to minimize chemical reactivity as diisocyanates react with OH groups which are present in other potential vehicles such as olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…While those studies evaluated the elicitation phase of the allergic response, even fewer studies have described roles for miRNA in the sensitization phase of an allergic response. Anderson et al (2014) investigated global lymph node miRNA expression profiles in a murine model of dermal TDI sensitization. Increases were observed in miR-21, miR-22, miR-155, miR-126, miR-27b, miR-210, miR-31, and miR-301a expression after a single dermal sensitizing application of TDI.…”
Section: Epigenetic Mediators Of Chemical Allergy In the Skinmentioning
confidence: 99%